Preparation method and application of vinyl-terminated methyl bromo-phenyl polysiloxane
By using end vinyl methyl bromide phenyl polysiloxane as base glue, silicone foam is prepared, which solves the problem of difficult to improve flame retardant performance and short service life in the prior art, and achieves high flame retardant performance and low The effect of compression and permanent deformation extends the service life of silicone foam.
Patent Information
- Application Number
- CN202411360804.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
AI Technical Summary
When existing silicone foams improve flame retardant performance, they need to add a large amount of flame retardant filler, which leads to a significant increase in compression and permanent deformation of silicone foams and significantly reduces service life.
Silicone foam is prepared by bromine modification and polymerization reaction by using end vinyl methyl bromide phenyl polysiloxane as the base gel to improve its flame retardant performance, and without adding a large amount of flame retardant filler, Add a small amount of porcelain filler to increase the limit oxygen index.
Without adding flame retardant filler, the limit oxygen index of silicone foam reaches 30%, and after adding a small amount of porcelain filler, it can reach about 37%, which meets the requirements of the working conditions. At the same time, the compression and permanent deformation are less than 3%, which extends the use life.
Smart Images

Figure CN119431801A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicone rubber, and specifically relates to a preparation method and application of terminal vinylmethylbromophenyl polysiloxane. Background Art
[0002] Silicone rubber is widely used in transportation, aerospace and other fields due to its excellent insulation, weather resistance, and high and low temperature resistance. Many usage scenarios have high requirements for the flame retardant properties of silicone rubber, especially for silicone foam used for cushioning and sealing. Since its porous structure increases the specific surface area, the flame retardant properties are often difficult to meet the requirements. The current mainstream solution is to add a large amount of flame retardant fillers to the material. The problem with this approach is that the addition of a large amount of fillers will cause the compression permanent deformation of the silicone foam to increase significantly, which will cause the service life of the silicone foam mainly used for cushioning, shock absorption, and sealing to be greatly reduced. Summary of the invention
[0003] In order to solve the technical problems existing in the prior art, the purpose of the present invention is to provide a preparation method and application of terminal vinylmethyl brominated phenyl polysiloxane.
[0004] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:
[0005] A method for preparing terminal vinylmethyl bromophenyl polysiloxane comprises the following steps:
[0006] The first step is to bromine-modify octaphenylcyclotetrasiloxane.
[0007] Add octaphenylcyclotetrasiloxane, liquid bromine and iron powder into a reaction container for reaction, wash the bottom liquid with water after the reaction is completed, separate the liquid to obtain a lower red liquid; then, pour the obtained red liquid into an alkali solution, react fully, separate the liquid to obtain an upper light yellow suspension, wash the light yellow suspension with water, separate the liquid to obtain an upper colorless liquid, add anhydrous sodium chloride to wash, filter and dry to obtain octabromophenylcyclotetrasiloxane;
[0008] The second step is to prepare terminal vinylmethyl bromophenyl polysiloxane using octabromophenyl cyclotetrasiloxane
[0009] Add octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and solvent into a reaction container, raise the temperature to a certain temperature, then add tetramethylammonium hydroxide, continue to raise the temperature to a certain temperature, add tetramethyldivinylsiloxane to react when the viscosity of the system increases, and continue to raise the temperature to a certain temperature after the reaction is completed. The obtained colorless transparent liquid is terminal vinylmethylbromophenyl polysiloxane.
[0010] Furthermore, in the first step, the weight ratio of the octaphenylcyclotetrasiloxane, liquid bromine and iron powder is 10:10:1-30:10:3.
[0011] Furthermore, in the second step, the weight ratio of the octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and the solvent is 2:5:10-4:17:26.
[0012] Furthermore, in the second step, octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and a solvent are added to the reaction vessel, the temperature is raised to 60-70° C., the vacuum degree is set to -0.08-0.09 MPa, maintained for 30-60 min, and then tetramethylammonium hydroxide is added.
[0013] Furthermore, in the second step, after tetramethylammonium hydroxide is added, the temperature is continued to rise to 110-120°C.
[0014] Furthermore, in the second step, when the viscosity increases to 100-120 cP, tetramethyl divinyl siloxane is added and the reaction is continued for 6-9 hours. After completion, the temperature is continued to be raised to 150-160° C. and maintained for 30-60 minutes. The obtained colorless transparent liquid is terminal vinyl methyl bromophenyl polysiloxane.
[0015] The invention also discloses application of terminal vinyl methyl brominated phenyl polysiloxane in silica gel foam.
[0016] The present invention also discloses a silica gel foam, comprising a component A and a component B, wherein the component A comprises the following raw materials in parts by weight:
[0017] 100 parts of base glue
[0018] Vulcanizing agent 1-5 parts
[0019] Ceramic filler 1-40 parts
[0020] 1-10 parts of porcelain additives
[0021] 1-20 parts of flame retardant filler;
[0022] The B component includes the following raw materials in parts by weight:
[0023] 100 parts of base glue
[0024] Inhibitor 0-5 parts
[0025] Foaming agent 1-20 parts
[0026] Ceramic filler 1-40 parts
[0027] 1-10 parts of porcelain additives
[0028] 1-20 parts of flame retardant filler;
[0029] The base glue is a mixture of methyl vinyl silicone oil and terminal vinyl methyl brominated phenyl polysiloxane, and the weight ratio of the methyl vinyl silicone oil to the terminal vinyl methyl brominated phenyl polysiloxane is 1:1-1:9.
[0030] Furthermore, the vulcanizing agent is platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, the porcelain filler is a mixture of wollastonite and muscovite, the flame retardant filler is a mixture of zinc borate and hydrotalcite, the foaming agent is a mixture of dimethylhydroxysilicone oil and polymethylhydrogensiloxane, and the inhibitor is tetramethyltetravinylcyclotetrasiloxane.
[0031] Furthermore, the weight ratio of wollastonite to muscovite is 3:2-1:1, and the particle size of muscovite is 5-15 μm; the weight ratio of zinc borate to hydrotalcite is 1:1-3:1, and the weight ratio of dimethylhydroxy silicone oil to polymethyl hydrogen siloxane is 1:1-1:4.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The invention discloses a preparation method and application of a terminal vinylmethyl bromophenyl polysiloxane. The terminal vinylmethyl bromophenyl polysiloxane is prepared by the following steps: the first step is to perform bromination modification on octaphenylcyclotetrasiloxane; the second step is to use octabromophenylcyclotetrasiloxane to prepare the terminal vinylmethyl bromophenyl polysiloxane; the invention uses the terminal vinylmethyl bromophenyl polysiloxane as a base rubber to prepare silicone foam, which can improve the flame retardant performance of the silicone foam, and the limiting oxygen index of the silicone foam can still reach 30% when no flame retardant filler is added, and the limiting oxygen index of the prepared silicone foam after adding a small amount of ceramic filler can reach about 37%, which fully meets the requirements of the use conditions, and at the same time, according to ASTMD1056, the compression permanent deformation after the test of 100°C, 50% compression and 168 hours can still be less than 3%, which can greatly improve the service life of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the reaction scheme of octabromophenylcyclotetrasiloxane of the present invention;
[0035] Figure 2 The following is a reaction scheme of the vinyl-terminated methyl brominated phenyl polysiloxane of the present invention. DETAILED DESCRIPTION
[0036] The present invention is described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0037] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.
[0038] On the one hand, the present invention discloses a method for preparing a terminal vinylmethyl brominated phenyl polysiloxane, such as Figure 1-2 As shown, the following steps are included:
[0039] The first step is to bromine-modify octaphenylcyclotetrasiloxane.
[0040] Octaphenylcyclotetrasiloxane, liquid bromine and iron powder are added to a reaction container for reaction. The weight ratio of octaphenylcyclotetrasiloxane, liquid bromine and iron powder is 10:10:1-30:10:3. After the reaction is completed, the bottom liquid is washed with water, and the lower red liquid is obtained by separation. Subsequently, the obtained red liquid is poured into an alkali solution, fully reacted, and the upper light yellow suspension is obtained by separation. The light yellow suspension is washed with water, and the upper colorless liquid is obtained by separation. Anhydrous sodium chloride is added for washing, filtering and drying to obtain octabromophenylcyclotetrasiloxane. The reaction route is:
[0041]
[0042] It should be noted that there is still a small amount of octaphenylcyclotetrasiloxane in the substance obtained in the first step. If you want to get a pure substance, you need to further distill it, but even without distillation, you can still get a good flame retardant effect. Different amounts of liquid bromine in the experiment will lead to different contents of octabromophenylcyclotetrasiloxane in the final result, and their flame retardant effects will have certain differences.
[0043] The second step is to prepare terminal vinylmethyl bromophenyl polysiloxane using octabromophenyl cyclotetrasiloxane
[0044] Octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and solvent are added to the reaction container, the weight ratio of octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and solvent is 2:5:10-4:17:26, the temperature is raised to 60-70°C, the vacuum degree is set to -0.08-0.09MPa, and maintained for 30-60min, then tetramethylammonium hydroxide is added, and the temperature is continued to rise to 110-120°C. When the viscosity of the system rises to 100-120cP, tetramethyldivinylsiloxane is added to react for 6-9h. After the reaction is completed, the temperature is continued to rise to 150-160°C and maintained for 30-60min. The obtained colorless transparent liquid is vinyl-terminated methylbromophenyl polysiloxane. The reaction route is:
[0045]
[0046] On the other hand, the present invention also discloses the application of terminal vinyl methyl brominated phenyl polysiloxane in silicone foam.
[0047] The silicone foam prepared using end-vinyl methyl brominated phenyl polysiloxane as the base has excellent flame retardant properties. Without adding flame retardant fillers, its limiting oxygen index can still reach 30%. After adding a small amount of ceramic fillers (a mixture of ceramic fillers and ceramic additives), the silicone foam prepared has a limiting oxygen index of about 37%, which fully meets the requirements of the use conditions. At the same time, according to ASTM D 1056, the compression permanent deformation after 100°C, 50% compression, and 168 hours of testing can still be less than 3%, which can greatly improve the service life of the product. In actual applications, an appropriate amount of flame retardant fillers will be added based on cost considerations. After adding flame retardant fillers, the limiting oxygen index can reach 40%, and the corresponding compression permanent deformation will also increase.
[0048] The present invention also discloses a silica gel foam, comprising a component A and a component B, wherein the component A comprises the following raw materials in parts by weight:
[0049] 100 parts of base glue
[0050] Vulcanizing agent 1-5 parts
[0051] Ceramic filler 1-40 parts
[0052] 1-10 parts of porcelain additives
[0053] 1-20 parts of flame retardant filler;
[0054] Component B includes the following raw materials in parts by weight:
[0055] 100 parts of base glue
[0056] Inhibitor 0-5 parts
[0057] Foaming agent 1-20 parts
[0058] Ceramic filler 1-40 parts
[0059] 1-10 parts of porcelain additives
[0060] 1-20 parts of flame retardant filler.
[0061] The base rubber is a mixture of methyl vinyl silicone oil and terminal vinyl methyl brominated phenyl polysiloxane, and the weight ratio of the methyl vinyl silicone oil to the terminal vinyl methyl brominated phenyl polysiloxane is 1:1-1:9.
[0062] The vulcanizing agent is platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, preferably 1-2 parts.
[0063] The ceramic filler is a mixture of wollastonite and muscovite. The weight ratio of wollastonite to muscovite is 6:4. The particle size of muscovite is 5-15μm and the density is 2.8g / cm 3 .
[0064] The ceramic additive is glass powder with a particle size of 2.5 μm and a density of 2.7 g / cm 3 .
[0065] The flame retardant filler is a mixture of zinc borate and hydrotalcite, the weight ratio of the zinc borate to the hydrotalcite is 1:1-3:1, the average particle size of the zinc borate is 50nm, and the average particle size of the hydrotalcite is 50nm.
[0066] The foaming agent is a mixture of dimethylhydroxy silicone oil and polymethyl hydrogen siloxane, and the weight ratio of the dimethylhydroxy silicone oil to the polymethyl hydrogen siloxane is 1:1-1:4.
[0067] The inhibitor is tetramethyltetravinylcyclotetrasiloxane, preferably 0.5 parts.
[0068] A method for preparing a silicone foam comprises the following steps:
[0069] The A component and the B component are uniformly mixed in a weight ratio of 1:1, and reacted at room temperature for 10-30 minutes to obtain a refractory porcelain-forming silicone foam with low compression permanent deformation.
[0070] Example 1
[0071] A method for preparing terminal vinylmethyl bromophenyl polysiloxane comprises the following steps:
[0072] The first step is to bromine-modify octaphenylcyclotetrasiloxane:
[0073] Add 100g of octaphenylcyclotetrasiloxane to a three-necked flask, then add 37g of liquid bromine, and finally add 10g of iron powder. After the reaction is completed, wash the bottom liquid with a large amount of water, separate the liquid to obtain a lower red liquid, pour the obtained red liquid into a 10% sodium hydroxide solution, fully react, separate the liquid to obtain an upper light yellow suspension, wash the obtained light yellow suspension with a large amount of water, separate the liquid to obtain an upper colorless liquid, add anhydrous sodium chloride to wash, filter and dry to obtain octabromophenylcyclotetrasiloxane. The reaction route is:
[0074]
[0075] It should be noted that there is still a small amount of octaphenylcyclotetrasiloxane in the substance obtained in the first step. Further distillation is required to obtain a pure substance, but even without distillation, a good flame retardant effect can still be obtained. The different amounts of liquid bromine used in the experiment will lead to different contents of octabromophenylcyclotetrasiloxane in the final result, and the flame retardant effects will have certain differences.
[0076] In the second step, octabromophenyl cyclotetrasiloxane is used to prepare terminal vinyl methyl bromophenyl polysiloxane:
[0077] Add 18g octamethylcyclotetrasiloxane, 45g octabromophenylcyclotetrasiloxane, and 100ml xylene solvent to a three-necked flask, heat to 65°C, vacuum degree is -0.08MPa, keep for 30min, then add 0.5wt% tetramethylammonium hydroxide TMAH, heat to 110°C, add 1g tetramethyldivinylsiloxane when the viscosity of the system rises to 100cP, continue to react for 8h, continue to heat to 150°C after completion, keep for 30min, and the obtained colorless transparent liquid is terminal vinylmethylbromophenyl polysiloxane. The reaction route is:
[0078]
[0079] Example 2
[0080] A silicone foam, comprising component A and component B, wherein component A comprises the following raw materials in parts by weight:
[0081] 100 parts of base glue
[0082] Platinum (0)-1,3-Diethylene-1,1,3,3-tetramethyldisiloxane curing agent 1 part
[0083] 20 parts of porcelain filler
[0084] 3 parts of porcelain additive
[0085] 5 parts of flame retardant filler;
[0086] Component B includes the following raw materials in parts by weight:
[0087] 100 parts of base glue
[0088] Tetramethyltetravinylcyclotetrasiloxane inhibitor 0.5 parts
[0089] 5 parts of foaming agent
[0090] 20 parts of porcelain filler
[0091] 3 parts of porcelain additive
[0092] 5 parts of flame retardant filler.
[0093] The base rubber is a mixture of methyl vinyl silicone oil and the terminal vinyl methyl brominated phenyl polysiloxane obtained in Example 1, and the weight ratio of the methyl vinyl silicone oil to the terminal vinyl methyl brominated phenyl polysiloxane is 1:9.
[0094] The ceramic filler is a mixture of wollastonite and muscovite. The weight ratio of wollastonite to muscovite is 6:4. The particle size of muscovite is 5μm and the density is 2.8g / cm 3 .
[0095] The ceramic additive is glass powder with a particle size of 2.5 μm and a density of 2.7 g / cm 3 .
[0096] The flame retardant filler is a mixture of zinc borate and hydrotalcite, the weight ratio of the zinc borate to the hydrotalcite is 1:1, the average particle size of the zinc borate is 50 nm, and the average particle size of the hydrotalcite is 50 nm.
[0097] The foaming agent is a mixture of dimethylhydroxy silicone oil and polymethylhydrogen siloxane, and the weight ratio of the dimethylhydroxy silicone oil to the polymethylhydrogen siloxane is 1:1.
[0098] A method for preparing a silicone foam comprises the following steps:
[0099] The A component and the B component are uniformly mixed in a weight ratio of 1:1, and reacted at room temperature for 10 minutes to obtain a refractory porcelain-forming silicone foam with low compression permanent deformation.
[0100] Comparative Example 1
[0101] The difference between this comparative example and Example 2 is that the base rubber of this comparative example is methyl vinyl silicone oil, and the rest is the same as Example 2.
[0102] Comparative Example 2
[0103] The difference between this comparative example and Example 2 is that the base rubber of this comparative example is methylphenyl silicone oil, and the rest is the same as Example 2.
[0104] The test results of Example 2 and Comparative Examples 1-2 are shown in Table 1.
[0105] Table 1
[0106] Limiting oxygen index Compression set Example 2 36.5% 1.86% Comparative Example 1 29.3% 5.49% Comparative Example 2 31.6% 4.13%
[0107] As can be seen from Table 1, the flame retardant properties of the silicone foam prepared using terminal vinyl methyl bromophenyl polysiloxane and methyl vinyl silicone oil as the base glue are excellent, and the limiting oxygen index can reach 36.5%. According to ASTM D 1056, the compression permanent deformation is less than 3% after 100°C, 50% compression, and 168 hours of testing. The flame retardant properties of the silicone foam prepared using methyl vinyl silicone oil or methyl phenyl silicone oil alone as the base glue are poor, the limiting oxygen index is lower than 32%, and the compression permanent deformation is greater than 3%, indicating that only by using terminal vinyl methyl bromophenyl polysiloxane and methyl vinyl silicone oil as the base glue can the silicone foam required by the present invention be prepared.
[0108] Parts or structures not specifically described in the present invention may adopt existing technologies or existing products and will not be described in detail here.
[0109] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a vinyl-terminated methyl brominated phenyl polysiloxane, characterized in that: The following steps are involved: The first step is to bromine-modify octaphenylcyclotetrasiloxane. Add octaphenylcyclotetrasiloxane, liquid bromine and iron powder into a reaction container for reaction, wash the bottom liquid with water after the reaction is completed, separate the liquid to obtain a lower red liquid; then, pour the obtained red liquid into an alkali solution, react fully, separate the liquid to obtain an upper light yellow suspension, wash the light yellow suspension with water, separate the liquid to obtain an upper colorless liquid, add anhydrous sodium chloride to wash, filter and dry to obtain octabromophenylcyclotetrasiloxane; The second step is to prepare terminal vinylmethyl bromophenyl polysiloxane using octabromophenyl cyclotetrasiloxane Add octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and solvent into a reaction container, raise the temperature to a certain temperature, then add tetramethylammonium hydroxide, continue to raise the temperature to a certain temperature, add tetramethyldivinylsiloxane to react when the viscosity of the system increases, and continue to raise the temperature to a certain temperature after the reaction is completed. The obtained colorless transparent liquid is terminal vinylmethylbromophenyl polysiloxane.
2. The method for preparing a vinyl-terminated methyl brominated phenyl polysiloxane according to claim 1, characterized in that: In the first step, the weight ratio of octaphenylcyclotetrasiloxane, liquid bromine and iron powder is 10: 10:1-30:10:3。 3. The method for preparing a vinyl-terminated methyl brominated phenyl polysiloxane according to claim 1, characterized in that: In the second step, the weight ratio of the octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and the solvent is 2:5:10-4:17:
26.
4. The method for preparing a vinyl-terminated methyl brominated phenyl polysiloxane according to claim 1, characterized in that: In the second step, octamethylcyclotetrasiloxane, octabromophenylcyclotetrasiloxane and solvent are added to the reaction vessel, the temperature is raised to 60-70° C., the vacuum degree is set to -0.08-0.09 MPa, and maintained for 30-60 min, and then tetramethylammonium hydroxide is added.
5. The method for preparing a vinyl-terminated methyl brominated phenyl polysiloxane according to claim 1, characterized in that: In the second step, after adding tetramethylammonium hydroxide, the temperature is continued to rise to 110-120°C.
6. The method for preparing a vinyl-terminated methyl brominated phenyl polysiloxane according to claim 1, characterized in that: In the second step, when the viscosity increases to 100-120 cP, tetramethyl divinyl siloxane is added and the reaction is continued for 6-9 hours. After completion, the temperature is continued to rise to 150-160° C. and maintained for 30-60 minutes. The obtained colorless transparent liquid is terminal vinyl methyl bromophenyl polysiloxane.
7. Use of the terminal vinylmethyl brominated phenyl polysiloxane according to any one of claims 1 to 6 in silicone foam.
8. The silicone foam according to claim 7, characterized in that: It comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 100 parts of base glue Vulcanizing agent 1-5 parts Ceramic filler 1-40 parts 1-10 parts of porcelain additives 1-20 parts of flame retardant filler; The B component includes the following raw materials in parts by weight: 100 parts of base glue Inhibitor 0-5 parts Foaming agent 1-20 parts Ceramic filler 1-40 parts 1-10 parts of porcelain additives 1-20 parts of flame retardant filler; The base glue is a mixture of methyl vinyl silicone oil and terminal vinyl methyl brominated phenyl polysiloxane, and the weight ratio of the methyl vinyl silicone oil to the terminal vinyl methyl brominated phenyl polysiloxane is 1:1-1:
9.
9. The silicone foam according to claim 8, characterized in that: The vulcanizing agent is platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, the porcelain filler is a mixture of wollastonite and muscovite, the flame retardant filler is a mixture of zinc borate and hydrotalcite, the foaming agent is a mixture of dimethylhydroxy silicone oil and polymethyl hydrogen siloxane, and the inhibitor is tetramethyltetravinylcyclotetrasiloxane.
10. The silicone foam according to claim 9, characterized in that: The weight ratio of wollastonite to muscovite is 3:2-1:1, and the particle size of muscovite is 5-15 μm; the weight ratio of zinc borate to hydrotalcite is 1:1-3:1, and the weight ratio of dimethylhydroxy silicone oil to polymethyl hydrogen siloxane is 1:1-1:4.